Integration of urban knowledge through visibility studies and pedestrian behavior analysis in Old Bazaar in Skopje - Gievska, Sonja; Marina, Ognen; Leduc, Thomas; Rabino, Giovanni; Karanakov, B (EDP Sciences, 2012)
The series of studies that are focused on the Old Bazaar – the historic and protected district in city of Skopje, exercise the complex spatial analysis or the urban environment with use of models of visibility, patterns of spatial configuration and pedestrian behavior as scientific knowledge and research tools for better understanding of the processes that are shaping our cities. An integrated knowledge base has been proposed as the basis for urban models, being the container of a variety of traceable information needed for exhaustive description of the urban context that can provide a scientific platform for more sustainable management and development of urban protected areas.